Unilateral breast enlargement in males during adolescence (10-19 years): Review of current literature and personal experience: Unilateral breast enlargement during adolescence - De Sanctis, Vincenzo; Soliman, Ashraf T.; Tzoulis, Ploutarchos; Daar, Shahina; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Abstract. Idiopathic unilateral breast enlargement (UBE) in males is a, commonly overlooked, diagnosis of exclusion that requires careful history, meticulous physical examination, and pertinent laboratory studies to exclude the possible pathologic causes. The aims of the present update are to review the current literature on UBE in subjects during adolescent age (10-19 years) in 18 cases, and to report the personal experience in 13 adolescents referred to our unit during the last four decades. In total, our survey and personal experience include 31 UBE cases, 10 of whom (32.2 %) being idiopathic or familial gynecomastia (GM). In 3/31 (9.6%) UBE was due to breast sarcoma/ carcinoma; one patient (11-years old) had a 5-year history of painless lump in the right breast, which increased gradually in size followed by bloody nipple discharge. In the personal cases of 13 adolescents, a moderate to marked UBE was secondary to: treatment with androgens (2 β-thalassemic patients with hypogonadism), high estrogen/androgen ratio in 2 Klinefelter syndrome patients, peripheral aromatization of androgens in 1 patient with non-classical 21-hydroxylase deficiency (NC-21-OH-D). One patient had subareolar hematoma due to injury. In 2 patients (15,3%) marked UBE was due to cystic lymphangioma (histologically proved). Furthermore, 5 patients were characterized as idiopathic UBE In clinical practice, the persistence of UBE for long period before diagnosis necessitates attention and further evaluation. Underlying causes should be treated, when possible, while surgery can be offered to patients with persistent or atypical signs and/or symptoms of UBE. For the optimal management of this condition, better collaboration between primary care physician and specialists is mandatory.